2022
DOI: 10.1111/jonm.13622
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership and performance of public hospitals: Trust in the leader and psychological empowerment of nurses

Abstract: Aims: This study examines the effect of servant leadership on the performance of the hospital through the mediating effect of trust in the leader. It further analyses the moderating role of psychological empowerment. Background: Hospitals in Pakistan experience a severe shortage of nurses. Nurses are overworked and need support to provide quality patient care. Servant leadership, which focuses on the growth and development of followers, is of relevance in such context. Methods: A sample of 339 registered nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Nonetheless, the nature of nursing leadership styles, how nursing leadership should be implemented, and its associated outcomes remain under-researched (Bai & Bai, 2023;Cummings et al, 2018). Therefore, this study focuses on servant leadership, a novel leadership type that has received scant attention in the nursing domain (Saleem et al, 2022;Xiao et al, 2023). We found that servant leadership did not directly influence nurses' in-role performance (Model 3, b = −0.023, p = .681), but through a two-mediator sequential mediation chain.…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the nature of nursing leadership styles, how nursing leadership should be implemented, and its associated outcomes remain under-researched (Bai & Bai, 2023;Cummings et al, 2018). Therefore, this study focuses on servant leadership, a novel leadership type that has received scant attention in the nursing domain (Saleem et al, 2022;Xiao et al, 2023). We found that servant leadership did not directly influence nurses' in-role performance (Model 3, b = −0.023, p = .681), but through a two-mediator sequential mediation chain.…”
Section: Ta B L Ementioning
confidence: 99%
“…In the nursing context, leadership strongly impacts nurses' outcomes and work experience (Luo et al, 2022). Nurse leaders contribute to work environments that promote high-quality patient care (Saleem et al, 2022), nurse well-being (Boamah, 2022) and performance (Eva et al, 2019). For example, Blake et al (2013) found that support from nursing leaders was strongly associated with job satisfaction as they support nurses' autonomy and control over their practice (Duffield et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Servant leadership has benefits and drawbacks. Benefits include development of a strong team culture, strong relationships, enhanced team confidence (Asuna, 2023), and trust (Saleem et al, 2022). In addition, servant leadership has demonstrated positive correlations with organizational outcomes (Yasir & Jan, 2022), collaboration (Tagliareni et al, 2022), reduced burnout (Ma et al, 2021), job satisfaction and engagement (Specchia et al, 2021), and overall nurse well-being (Niinihuhta & Häggman-Laitila, 2021).…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Consequently, the theory lacks scientific and empirical evidence to justify its widespread acceptance. Although there is a vast volume of research covering servant leadership under different conditions, there still needs to examine the impact of servant leadership on job performance (Lee et al, 2020;Saleem et al, 2022). Thus, the positive side of servant leadership and its consequences are still to be uncovered and understood, especially in this study's context; the Jordanian environment.…”
Section: Introductionmentioning
confidence: 96%
“…The world is witnessing hyper-turbulent business, social and economic changes, and significant global health and safety issues due to Covid 19 and various global crisis that affect most organizations (Saleem et al, 2022;The Global Risks Report, 2022;Ruiz-Palomino et al, 2022). Accordingly, business leaders need to respond by promoting the most effective measures for economic upheaval and taking actions that maximize economic recovery (Fernandez & Shaw, 2020).…”
Section: Introductionmentioning
confidence: 99%